INTEGRATION OF THE ROLE OF AUTHORITY FIGURES IN EMBEDDING CHLIDREN’S CHARACTER EDUCATION IN PANDEMIC ERA - Muhyatun, Muhyatun; Budianto, Ahmad Andry (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Character education has become the spirit of education in Indonesia since the old era, the new era and until now. Since the corona virus pandemic took place, the implementation of character education has encountered challenges and obstacles that not only involve students but also teachers, educators, and parents. These obstacles and challenges are in the form of distance learning and also the quality of inculcating moral values ​​that are accepted by students. Therefore, the purpose of this study is to conduct a study of the importance of integrating the roles of authority figures, be it parents, teachers and other authority figures, in instilling and developing character education in children during the pandemic. The research was conducted using library research research methods. The results of the research conducted indicate that all educational institutions, both formal education such as schools or colleges, as well as non-formal education environments such as families and communities, must be able to be integrated, collaborate and synergize in the implementation of character education. The role of both, as a place where authority figures take advantage of their authority, must be utilized as well as possible in order to create a pattern of inculcating good values ​​or character from students themselves, from their families and communities. Thus, education in Indonesia is education that is able to give birth to humans who can also humanize humans.